English High-stakes Testing in Indonesia: Friend or Foe? - Puspitasari, Maya; Pelawi, Muhammad Arifin (UNIB Press, 2023)
The Education Ministry has eliminated standardised high-stakes testing called Ujian Nasional (UN) since 2021 throughout schools all around Indonesia. However, it might be practical to look backwards at the UN and its implementation with the impact it gives on the teachers. This article has a concern about the washback consequences of a high-stakes exam on teachers. The effects were investigated within the specific context of the 2016 UN for students in Indonesia at the junior secondary level. A semi-structured interview with eight English teachers was set up to explore the teachers' perceptions towards the UN. Regarding feelings, all participants shared divergent feelings ranging from disinterested to excessive levels of fear or anxiety and mixed feelings. The data also showed mixed opinions, both positive and negative, regarding the examination. The students were thought to be motivated to study because the examination was used for selection purposes. The results did, however, also imply that the students' performance on the national exam was thought to have been assessed unfairly. The instructors demonstrated how the exam affected their teaching roles and methods. Making the national exam a low-stakes test was one of the suggestions made by attendees to enhance it.